2019
DOI: 10.3389/fcimb.2019.00091
|View full text |Cite
|
Sign up to set email alerts
|

Toward DNA-Based T-Cell Mediated Vaccines to Target HIV-1 and Hepatitis C Virus: Approaches to Elicit Localized Immunity for Protection

Abstract: Human immunodeficiency virus (HIV)-1 and hepatitis C virus (HCV) are major contributors to the global disease burden with many experts recognizing the requirement of an effective vaccine to bring a durable end to these viral epidemics. The most promising vaccine candidates that have advanced into pre-clinical models and the clinic to eliminate or provide protection against these chronic viruses are viral vectors [e.g., recombinant cytomegalovirus, Adenovirus, and modified vaccinia Ankara (MVA)]. This raises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 96 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…Many reports have shown that CD8+ T cells play a very important role in the control of viral replication during the acute phase of human immunodeficiency virus (HIV)−1 infection, contributing to the initial control of infection 1,3-7 . Thus, a large number of current studies are focused on the search of new therapies with the aim of inducing a potent and effective HIV specific CD8+ T cell response [8][9][10] .…”
Section: Cd300a Receptor Is Found On Different Cd8+ T Cell Subsets Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have shown that CD8+ T cells play a very important role in the control of viral replication during the acute phase of human immunodeficiency virus (HIV)−1 infection, contributing to the initial control of infection 1,3-7 . Thus, a large number of current studies are focused on the search of new therapies with the aim of inducing a potent and effective HIV specific CD8+ T cell response [8][9][10] .…”
Section: Cd300a Receptor Is Found On Different Cd8+ T Cell Subsets Anmentioning
confidence: 99%
“…Many reports have shown that CD8+ T cells play a very important role in the control of viral replication during the acute phase of human immunodeficiency virus (HIV)−1 infection, contributing to the initial control of infection 1,3-7 . Thus, a large number of current studies are focused on the search of new therapies with the aim of inducing a potent and effective HIV specific CD8+ T cell response [8][9][10] .After antigen recognition and subsequent activation, CD8+ T cells up-regulate the expression of inhibitory receptors with the aim of preventing an excessive response that, if not properly regulated, could be harmful to the host 11,12 . During chronic stimulation, as for example persistent exposure to HIV antigens, CD8+ T cells became progressively dysfunctional and exhausted, and the expression of inhibitory receptors persists 13 .…”
mentioning
confidence: 99%
“…A variety of vaccines have been designed for HCV without using E1E2, instead utilizing antigens from core [ 131 , 132 , 133 ], p7 [ 134 ] or non-structural proteins [ 135 , 136 ], which have been evaluated for stimulation of T cell responses [ 137 , 138 ], with a focus on DNA vaccines [ 139 , 140 , 141 ] or expression with viral vectors [ 142 , 143 ]. One T cell-based vaccine with viral vectored non-structural proteins has been tested in a phase 1/2 clinical trial for protection against HCV infection in healthy at-risk individuals; while it failed to prevent chronic HCV infection, it did induce HCV-specific T cell responses [ 144 ].…”
Section: Design Approachesmentioning
confidence: 99%
“…Nucleic acid based-vaccines present numerous advantages over traditional vaccine approaches: (1) No issues associated with misfolding of proteins in recombinant protein vaccines or with high manufacture costs; (2) No infectious risks that might be associated with live-attenuated or inactivated whole virus vaccines; (3) They are able to activate both arms of the immune response (humoral and cellular); (4) The expression of antigens resembles natural epitopes; (5) In a single injection, multiple genes can be delivered; and (6) If multiple doses are needed, unlike the use of recombinant virus-based vaccines, there is no risk of anti-vector immunity[ 39 , 237 , 238 ].…”
Section: Approaches To Design Vaccine Candidates For Hcvmentioning
confidence: 99%
“…In general, effective vaccine candidates should stimulate generation of nAbs and a proper cellular immune response. In order to design vaccines that elicit protective immunity against HCV, it is of utmost importance to consider the virus tropism (mainly hepatocytes), transmission route (parenteral transmission through contaminated blood) and pathogenesis[ 39 ].…”
Section: Introductionmentioning
confidence: 99%